"Different pretreatments of beach-cast seaweed for biogas production". (15th August 2022) - Lymperatou, Anna; Engelsen, Thor K.; Skiadas, Ioannis V.; Gavala, Hariklia N.
Abstract: The increasing amount of seaweed accumulated in the coasts calls for a proper disposal or treatment in order to reduce secondary pollution effects. Anaerobic digestion of seaweed is a treatment technology that simultaneously produces biogas, supporting the further expansion of the renewable energy production through sustainable bioresources. In this study, three pretreatments (alkaline, hydrothermal and thermo-acidic) were applied on beach-cast seaweed of the Baltic Sea in order to improve the methane yield. The thermo-acidic pretreatment resulted to the highest increase of the methane yield (78% higher than the raw seaweed), while the alkaline pretreatment resulted to a 36% increase of the methane yield and to the highest reduction of the methane production cost compared to raw seaweed based on a preliminary economic assessment. Determination of the different sugars and sugar acids of the seaweed before and after the pretreatments assisted in understanding the effects of each pretreatment on the seaweed matrix. Graphical abstract: Image 1 Highlights: Beach-cast seaweed was analyzed for its composition in sugars and sugar acids. A hydrothermal, an alkaline and a thermo-acidic pretreatment was applied. The thermo-acidic pretreatment resulted to the highest increase of CH4 yield (78%). The hydrolysis rate of seaweed was improved by all the pretreatments applied. Alkaline pretreatment resulted to the lowest cost of CH4 production from seaweed.